Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Open Education Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (Zenodo, 2020)
This curated list defines open educational resources, offers background on open source licensing, and provides a review of OER relevant to the context of Ghana in response to an EdTech Hub helpdesk request. This document does not intend to set out a comprehensive list of OER used by teachers, students, parents or other stakeholders; rather, this document will identify exemplars of OER provided they are relevant to the Ghanaian context and focus on: reaching marginalised learners through offline or online content; reaching marginalised learners through mass media; using OER for teacher education; further useful resources and methods of implementing OER.

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: Read; Teacher education and training; _r:AddedByZotZen

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen